Analisis Perhitungan Harga Pokok Produksi pada Usaha Penjualan Ceker Lunak di Malang - Heri Purnomo; Ali Syaifulloh (STIE Malangkucecwara, 2015)
Mie Ceker Lunak is a business that aims to sell processed foods such as chicken noodle with soft claw mixture also oriented on profit and not be separated from issues profit achievement, and payback. Thus, in calculating the cost of production and collection costs incurred to buy noodles, chicken, chicken claw and seasoning as its main ingredient, the cost incurred is supposed to be used as an element of the calculation of the establishment cost of the product to venture capital returns claw soft noodles with production capacity resulting from. The purpose of this paper aims to determine the production cost price calculation claw soft noodles, because the cost of production as a calculation tool in decision making. Soft noodles claw effort in making the report the cost of production has not been able to show the cost of production in accordance with the collection of production costs. On the other hand, the authors assume that the calculation of the cost of production enterprises claw noodles right software can know the cost of an adequate sales and profit analysis of the desired impact on the company.